CONSTITUTIONAL REFORM IN GEORGIA AS A RESULT OF ITS POLITICAL INSTABILITY - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2011)
In the twenty years that have elapsed since Georgia gained its independence, it has failed to stabilize its political system; the republic is busy looking for an adequate model of political governance and territorial-administrative division; there is no flexible and effective electoral system acceptable to all.Year after year, the Constitution acquires amendments and addenda which never resolve the political contradictions and merely add to the confusion.For over twenty years now, Georgian politicians have been discussing and disagreeing about the new electoral systems and constitutional amendments and addenda; they prefer to call their disagreements “nation-building.” The republic’s citizens have become lost in a dense forest of legal formulas and political regulations.In fact, these disagreements are the outcrop of a never-ending power struggle that does not allow the republic to stabilize its political system.